Kelayakan Usaha Produk Agroindustri Kentang Dari Aspek Pemasaran Di Desa Pinasungkulan Kecamatan Modoinding Kabupaten Minahasa Selatan - Soputan, Angelia; Lolowang, Tommy Ferdy; Baroleh, Jenny (Sam Ratulangi University, 2024)
The purpose of the study was to analyze and determine the amount of production costs, revenue, profit and business feasibility of potato agro-industry in Pinasungkulan Village, Modoinding District, South Minahasa Regency. The research lasted for 2 months from September to October 2023. The data collected was obtained through primary data by conducting direct interviews at the research location to the leader (owner) of the Tanding Agroindustry company in Pinasungkulan Village, Modoinding District, and secondary data obtained from business bookkeeping records, literature/internet and journals related to the research. The method used in this research is the case study method. The results showed that the profit from the sparring potato product business in Pinasungkulan Village, Modoinding Subdistrict, South Minahasa Regency was IDR1.810.833 per week, in a month amounting to IDR7.243.332. The non-financial feasibility of tanding agro-industry business in market and marketing aspects and technical aspects is feasible. The financial feasibility of this agro-industry business is feasible with an R/C Ratio of 1,55 > 1.